2020
DOI: 10.1039/c9sm01740b
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-sectional focusing of red blood cells in a constricted microfluidic channel

Abstract: Constrictions in blood vessels and microfluidic devices can dramatically change the spatial distribution of passing cells or particles and are commonly used in biomedical cell sorting applications. However, the three-dimensional nature of cell focusing in the channel cross-section remains poorly investigated. Here, we explore the cross-sectional distribution of living and rigid red blood cells passing a constricted microfluidic channel by tracking individual cells in multiple layers across the channel depth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…The implementation of a geometrical constriction has been demonstrated to focus cells towards the centerline of the device when the width of the channel is subsequently increased. 26,27 . Finally, in order to obtain a single file of cells, Tsai et al have used a 4.5µm wide and 30 µm long geometrical restriction with a width to center RBCs and align them so they would enter the evaluation zone on the same streamline 28 .…”
Section: A Centering Effect Of the Geometrymentioning
confidence: 99%
“…The implementation of a geometrical constriction has been demonstrated to focus cells towards the centerline of the device when the width of the channel is subsequently increased. 26,27 . Finally, in order to obtain a single file of cells, Tsai et al have used a 4.5µm wide and 30 µm long geometrical restriction with a width to center RBCs and align them so they would enter the evaluation zone on the same streamline 28 .…”
Section: A Centering Effect Of the Geometrymentioning
confidence: 99%
“…Faiver et al (2006) also found that using a contraction-expansion channel had a high impact on the CFA formation [21]. Abay et al (2020) use a constricted channel to focus 4% of RBCs suspended in PBS [34]. They observed no inertial focusing before the contraction, but the focusing effect was observed due to the narrow section, increasing the velocity.…”
Section: Flow Rate Simulation and Experimentsmentioning
confidence: 99%
“…We use two commercial pressure controllers, the Elveflow OB1-MK3 and the Fluigent Flow-EZ, to drive fluid through a microfluidic device. Both pressure devices have been used in various microfluidic studies 11,12,[20][21][22][23] and are referred to as OB1 pump and as Flow-EZ pump throughout this study. The pressure controller outlet is connected to a 1.5 mL tube containing the fluid sample.…”
Section: Microfluidic Setupmentioning
confidence: 99%